2005
DOI: 10.1002/14651858.cd004363.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant prevention of postnatal depression

Abstract: It is not possible to draw any clear conclusions about the effectiveness of antidepressants given immediately postpartum in preventing postnatal depression and, therefore, cannot be recommended for prophylaxis of postnatal depression, due to the lack of clear evidence. Larger trials are needed which also include comparisons of antidepressant drugs with other prophylactic treatments to reflect clinical practice, and examine adverse effects for the foetus and infant, as well as assess womens' attitudes to the us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Given the limited empirical evidence supporting use of antidepressant medication with PPD [1,22], there is a significant need to develop effective psychosocial treatment approaches. Recent meta-analyses of psychosocial interventions for PPD concluded that they have a moderate beneficial effect [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Given the limited empirical evidence supporting use of antidepressant medication with PPD [1,22], there is a significant need to develop effective psychosocial treatment approaches. Recent meta-analyses of psychosocial interventions for PPD concluded that they have a moderate beneficial effect [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…The studies which investigated antidepressants found that sertraline was more likely to exhibit preventative effects in developing postpartum depression and reduce the extent of depressive symptoms in the postpartum period. These studies found that sertraline was more effective in reducing the risk of developing postpartum depression and experiencing postpartum depressive symptoms compared to nortriptyline (Howard et al, 2005;Molyneaux et al, 2018;Pariser, Nasrallah, & Gardner, 1997). Other studies compared sertraline with a placebo in treating postpartum depression.…”
Section: Analysis Of Resultsmentioning
confidence: 99%
“…52 Yet, the small, voluntary, and select nature of the sample, as well as the lack of child outcome measures, indicate that more research is necessary. Biological approaches to preventing PPD also have been studied, but successful results are rare, 41,53 and, as noted previously, biological prevention approaches are often not well received by mothers because of concerns about the pass-through effects of medication on fetuses or infants. The extent to which maternal depression often coexists with other mental health problems (e.g., anxiety disorders or substance abuse) further complicates the challenge of designing effective prevention programs.…”
Section: The Issuementioning
confidence: 99%